Causality in the sciences - Illari, Phyllis McKay; Russo, Federica, Dr.; Williamson, Jon. (Oxford : Oxford University Press, 2011)
Why do ideas of how mechanisms relate to causality and probability differ so much across the sciences? Can progress in understanding the tools of causal inference in some sciences lead to progress in others? This book tackles these questions and others concerning the use of causality in the sciences.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Science -- Philosophy; Causation